Analisis Marjin Pemasaran Salak Pondoh di Kecamatan Turi Kabupaten Sleman - Caesari, Cecilia Elsa; Sutrisno, Joko; Antriyandarti, Ernoiz (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2021)
This study aims to identify the pattern of salak pondoh marketing channels, know the amount of cost, profit and marketing margin salak pondoh, analyze the factors that affect the marketing margin salak pondoh and know the level of efficiency economically from each marketing channel salak pondoh in Turi District Sleman. The basic method used in this study is descriptive and analytic method. Location of study is Turi District Sleman, because Turi Sub-district is the center of salak pondoh in Sleman District. The results showed that there are 3 (three) types of salak pondoh marketing channel. Channel I: Farmers → Wholesaler → Trader Outer City; Channel II: Farmers → Village Collector Traders → Wholesaler → Out of City Collector Trades; Channel III: Farmers → Export Collecting Traders → Mitra Turindo. The total marketing cost of marketing channels I, II, and III are Rp 720/kg, Rp 821/kg and Rp 1.101/kg. The total profit for marketing channels I, II, and III are Rp 180/kg, Rp 479/kg, and Rp 1.299/kg. The percentages of marketing margins for channels I, II, and III are 17,77%, 20,02%, and 31,58%. The factors that affect the marketing margin salak pondoh is marketing agencies. Marketing channel I is the most efficient marketing channel with marketing margin percentage value of 17,77% and farmer share value of 83,02%. Government should provide training of processing salak pondoh into snacks and farmers can register their garden to join export program.